Biophysical characterization of light-gated ion channels using planar automated patch clamp - Govorunova, Elena G.; Sineshchekov, Oleg A.; Brown, Leonid S.; Spudich, John L. (Frontiers in Molecular Neuroscience, 2022)
Channelrhodopsins (ChRs) are proteins that guide phototaxis in protists and exhibit light-gated channel conductance when their genes are heterologously expressed in mammalian cells. ChRs are widely used as molecular tools to control neurons and cardiomyocytes with light (optogenetics). Cation- and anion-selective ChRs (CCRs and ACRs, respectively) enable stimulation and inhibition of neuronal activity by depolarization and hyperpolarization of the membrane, respectively. More than 400 natural ChR variants have been identified so far, and high-throughput polynucleotide sequencing projects add many more each year. However, electrophysiological characterization of new ChRs lags behind because it is mostly done by time-consuming manual patch clamp (MPC). Here we report using a high-throughput automated patch clamp (APC) platform, SyncroPatch 384i from Nanion Technologies, for ChR research. We find that this instrument can be used for determination of the light intensity dependence and current-voltage relationships in ChRs and discuss its advantages and limitations.